The first hydrophilous cave-dwelling millipede from Serbia—Typhloiulus balcanicus sp. nov. (Diplopoda, Julida, Julidae) - Antić, Dragan Ž.; Dudić, Boris D.; Gajić, Mirjana R.; Lučić, Luka R. (Zootaxa, 2017)
As the fourth hydrophilous species of the genus Typhloiulus Latzel, 1884, the new species T. balcanicus Antić sp. nov. is described from two caves in the Stara Planina Mountains of Serbia. A brief discussion of the relationships between the new species and congeners with modified and unmodified mouthparts is presented, as well as short notes on the habitat of the new species and comments on other semiaquatic millipedes with modified mouthparts.